2016
DOI: 10.1038/ncb3393
|View full text |Cite
|
Sign up to set email alerts
|

The mammalian dynein–dynactin complex is a strong opponent to kinesin in a tug-of-war competition

Abstract: Kinesin and dynein motors transport intracellular cargos bidirectionally by pulling them in opposite directions along microtubules, through a process frequently described as a ‘tug of war’. While kinesin produces a 6 pN force, mammalian dynein was found to be a surprisingly weak motor (0.5–1.5 pN) in vitro, suggesting many dyneins are required to counteract the pull of a single kinesin. Mammalian dynein’s association with dynactin and Bicaudal-D2 (BICD2) activates its processive motility, but how this affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
241
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(280 citation statements)
references
References 40 publications
38
241
1
Order By: Relevance
“…Potential linkers to facilitate cooperation of dynein and kinesin 3 include Hook and Bicaudal, cargo adapter proteins that have been identified to interact with both dynein and kinesin 3 tail domains [41,69,125,126]. Interestingly, the presence of BICD2 increases the force generation and processivity of dynein/dynactin [127,128], demonstrating that these cargo adapter proteins regulate motor activity and could act as switches to control transport directionality within a complex containing two opposing motors. Other control mechanisms could come from accessory proteins such as kinesin binding protein (KBP), which has been shown to stimulate KIF1B, but inhibit KIF1A mediated bidirec tional transport [28,129].…”
Section: Cooperation Of Motorsmentioning
confidence: 99%
“…Potential linkers to facilitate cooperation of dynein and kinesin 3 include Hook and Bicaudal, cargo adapter proteins that have been identified to interact with both dynein and kinesin 3 tail domains [41,69,125,126]. Interestingly, the presence of BICD2 increases the force generation and processivity of dynein/dynactin [127,128], demonstrating that these cargo adapter proteins regulate motor activity and could act as switches to control transport directionality within a complex containing two opposing motors. Other control mechanisms could come from accessory proteins such as kinesin binding protein (KBP), which has been shown to stimulate KIF1B, but inhibit KIF1A mediated bidirec tional transport [28,129].…”
Section: Cooperation Of Motorsmentioning
confidence: 99%
“…Whereas individual mammalian dyneins in vitro very rarely exhibit processive behavior (the ability to take repeated steps along microtubules) (25)(26)(27)(28), dynein complexes bound to the accessory complex dynactin and a cargo adaptor frequently move processively over very long distances (25,(28)(29)(30). Once bound to dynactin and a cargo adaptor, processive movements of dynein are faster and the motor has a greater force output (28,31).…”
Section: Significancementioning
confidence: 99%
“…Very recently, it has also been demonstrated that one can directly crosslink a single, fluo-labeled kinesin with a single, fluo-labeled dynein via DNA hybridization. 21 Our tug-of-war model provides detailed predictions for the transport properties of such a two-motor system. One of these properties is the probability distribution p st j for the spatial separation of the two motors as displayed in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The fluctuating motor-motor separation L should be directly accessible to experimental studies when one combines the recently introduced crosslinking of one fluo-labeled kinesin and one fluo-labeled dynein via DNA hybridization 21 with advanced methods of fluorescence imaging such as FIONA. 29 In Fig.…”
Section: Steady State Properties Of Tug-of-warmentioning
confidence: 99%
See 1 more Smart Citation